Additive Role of a Potentially Reversible Cognitive Frailty Model and Inflammatory State on the Risk of Disability: The Italian Longitudinal Study on Aging - Solfrizzi, Vincenzo; Scafato, Emanuele; Lozupone, Madia; Seripa, Davide; Giannini, Michele; Sardone, Rodolfo; Bonfiglio, Caterina; Abbrescia, Daniela I; Galluzzo, Lucia; Gandin, Claudia; Baldereschi, Marzia; Di Carlo, Antonio; et al. (The American journal of geriatric psychiatry, 2017)
Cognitive frailty is a condition recently defined by operationalized criteria describing the simultaneous presence of physical frailty and mild cognitive impairment (MCI). Two subtypes for this clinical construct have been proposed: "potentially reversible" cognitive frailty (physical frailty plus MCI) and "reversible" cognitive frailty (physical frailty plus pre-MCI subjective cognitive decline). Here the prevalence of a potentially reversible cognitive frailty model was estimated. It was also evaluated if introducing a diagnosis of MCI in older subjects with physical frailty could have an additive role on the risk of dementia, disability, and all-cause mortality in comparison with frailty state or MCI condition alone, with analyses separately performed for inflammatory state. In 2,373 individuals from the population-based Italian Longitudinal Study on Aging with a 3.5-year-follow-up, we operationally categorized older individuals without dementia into four groups: non-frail/non-MCI, non-frail/MCI, frail/non-MCI, and frail/MCI. The prevalence of potentially reversible cognitive frailty was 1%, increasing with age and more represented in women than in men, and all groups were associated with significant increased incident rate ratios of dementia, disability, and mortality. A significant difference in rates of disability has been found between the MCI and non-MCI groups (contrasts of adjusted predictions: 0.461; 95% confidence interval: 0.187-0.735) in frail individuals with high inflammatory states (fibrinogen >339 mg/dL). In older individuals without dementia and with elevated inflammation, a potentially reversible cognitive frailty model could have a significant additional predictive effect on the risk of disability than the single conditions of frailty or MCI.